Peran Orangtua Dalam Membina Akhlak Anak Usia Dini Di Era 5.0 - Sundusiah (Kopertais Wilayah XV Lampung, 2022)
Consciously or not, the various changes that have occurred have in fact changed the culture of society and the way of life of the people. On the one hand, we live in a civilized society, but there are problems that threaten, one of which is the decline in society's character and morals as a result of the dynamics of today's all-technology world. Based on these problems, this study aims to examine the role of parents in fostering early childhood morals in the 5.0 era. This research is library research. The results of the study show that parents can help their children develop morals, either directly or indirectly. Immediate progress, for example, includes practicing commendable ethics, praying on time, being reliable, honest, not lying, and supervising children using cell phones. Second, avoid morally bad behavior. in everyday life, such as taking other people's belongings, fighting, betrayal, and other deviant acts. The conclusion, parents play an important role in preparing their children to become the next generation with strong religious and moral foundations.